Effects of the herbicide mesotrione applied in post-emergence on sorghum grown in second crop in the Goiás Southwest region, Brazil - Dias, André Rodrigues; Côrrea, Fernando Rezende; Silva, Nelmício Furtado da; Cavalcante, Wendson Soares da Silva; Ribeiro, Daniele Ferreira; Rodrigues, Estevão (Brazilian Journal of Science, 2023)
With the expansion of the sorghum culture and its market facility, field research was adopted to evaluate the effect of the herbicide Mesotrione isolated, in tank mixture and in commercial mixture with Atrazine applied in post-emergence in sorghum cultivated in second crop in goiano Southwest. The experiment was implemented at the Teaching, Research and Extension Farm of the UniBRAS College – Rio Verde – GO, in an Oxisol Vermelho Distróferrico (LVDf). The experimental design used was a randomized block, with 5 treatments and 4 replications. The treatments consisted of the use of different combinations between the herbicides Atrazine and Mesotrione. Crop phytotoxicity was evaluated at 7, 14, 21 and 28 days after application (DAA), carried out from the attribution of grades using a scale. With the results obtained it was verified that there was a significant difference for sorghum plant phytotoxicity with the use of herbicides in higher dosages. There was weed control when Mesotrione was applied at 21 DAA. At 7 and 14 DAA there was control with the use of Atrazine + Mesotrione, as well as better results in sorghum grain yield, when compared to the control and to Atrazine.